Penerapan Metode Pembelajaran Experiental Learning Berbantuan Media Audiovisual Untuk Meningkatkan Hasil Belajar Siswa - I Wayan Darmayoga (Edukasi: Jurnal Pendidikan Dasar, 2023)
This study aims to find out the application of the Experiential learning method assisted by audio visual media in order to improve the learning outcomes of class III students at Elemntary School Number 1 Penatih in the academic year 2022/2023. This study consists of two cycles, which is each cycle consisting of four stages, namely planning, action, observation/evaluation, and reflection. The subjects of this study were 34 students of grade III Elementary School Number 1 Penatih. The object of this study is the result of the learning in topic 2. The method in collecting the data in this study is the test method of learning outcomes. Based on the results of this study, it can be concluded that the average percentage of learning outcomes in topic 2 reaches 50% and classical completeness reaches 40%. After applying the Experiential learning method assisted by audio visual media in cycle I, the average percentage of learning outcomes reached 60%, and classical completeness reached 65%. With the improvement in cycle II, the average percentage of students' Topic 2 learning outcomes increased to 80% and classical completeness reached 90%.